Long-term health outcomes of allogeneic hematopoietic stem cell transplantation - Kelkar, Amar H.; Antin, Joseph H.; Shapiro, Roman M. (Frontiers in Oncology, 2023)
Background: Fifty years of hematopoietic cell transplantation (HCT) has ushered in an exciting era of cellular therapy and has led to enormous progress in improving the outcomes of patients with both malignant and non-malignant hematologic disease. As the survival of transplanted patients has increased, so has the recognition of long-term complications related to this therapy. Purpose: The goal of this review is to highlight some of the most common long-term complications of HCT. Data Sources: To this end, we have conducted a review of the published literature on the long-term complications of HCT encompassing the past 50 years. Study Selection: We have endeavored to include long-term complications reported in research articles, case series and case reports, reviews, and abstracts. We have focused primarily on adult allogeneic HCT, but have included some data from studies of pediatric allogeneic HCT as well. We have also prioritized the literature published in the last 15 years. Data Extraction: Key data supporting the onset and prevalence of the most common long-term complications was extracted. Limitations: While the list of long-term complications extracted and reported was comprehensive, it was not exhaustive. Conclusions: We have endeavored to highlight some of the most common long-term complications of HCT, the recognition and management of which constitutes an important part of HCT survivorship care.